Managing and coping with names of pleomorphic fungi in a period of transition - D.L. Hawksworth (IMA Fungus)
An explanation is provided of the recent changes in the International Code of Nomenclature for algae, fungi and plants relating to the ending of the separate naming of different states of fungi with a pleomorphic life-cycle. Issues relating to their implementation are discussed, including problems of defining “widely used”, author citations, proofs of holomorphy, typification, the preparation of “Lists of accepted and rejected names” (with a possible timetable), relationship to the existing processes of sanctioning and conservation or rejection, and steps to be considered for the future. This material is presented here to stimulate debate on the actions that should be taken by individuals, and responsible committees, in the current period of transition to a system of fungal nomenclature fit for the 21st century.